The Origins of Democratic Zionism. - Kaplan, Gregory B. (Routledge, 2019)
Cover -- Half Title -- Title -- Copyright -- Dedication -- Contents -- List of abbreviations -- Preface -- Acknowledgments -- Introduction: from democracy to democratic Zionism -- 1 Flawed democracy, the Aristotelian agricultural democracy and the Hebrew Republic -- 2 The medieval divine-right monarchy, an anti-Hebrew Republic -- 3 The divine-right Spanish monarchy and the conversos -- 4 The Hebrew Republic as an alternative to Habsburg rule and the emergence of Morteira, Barrios and Spinoza -- 5 The Hebrew Republic and democratic Zionism in the writings of Morteira -- 6 Morteira, Hobbes and the democratic Zionism of Spinoza and Barrios -- 7 Democratic Zionism and twenty-first-century Zionism -- Appendix: Treatise on the Truth of the Law of Moses, Chapters one, two, ten and eleven (translation into English by Gregory B. Kaplan) -- Index.